Analgesic Effect of Acetaminophen: A Review of Known and Novel Mechanisms of Action - Ohashi, Nobuko; Kohno, Tatsuro (Frontiers in Pharmacology, 2020)
Acetaminophen is one of the most commonly used analgesic agents for treating acute and chronic pain. However, its metabolism is complex, and its analgesic mechanisms have not been completely understood. Previously, it was believed that acetaminophen induces analgesia by inhibiting cyclooxygenase enzymes; however, it has been considered recently that the main analgesic mechanism of acetaminophen is its metabolization to N-acylphenolamine (AM404), which then acts on the transient receptor potential vanilloid 1 (TRPV1) and cannabinoid 1 receptors in the brain. We also recently revealed that the acetaminophen metabolite AM404 directly induces analgesia via TRPV1 receptors on terminals of C-fibers in the spinal dorsal horn. It is known that, similar to the brain, the spinal dorsal horn is critical to pain pathways and modulates nociceptive transmission. Therefore, acetaminophen induces analgesia by acting not only on the brain but also the spinal cord. In addition, acetaminophen is not considered to possess any anti-inflammatory activity because of its weak inhibition of cyclooxygenase (COX). However, we also revealed that AM404 induces analgesia via TRPV1 receptors on the spinal dorsal horn in an inflammatory pain rat model, and these analgesic effects were stronger in the model than in naïve rats. The purpose of this review was to summarize the previous and new issues related to the analgesic mechanisms of acetaminophen. We believe that it will allow clinicians to consider new pain management techniques involving acetaminophen.